Pendidikan Akhlak yang Terkandung dalam Buku “Yang Hilang dari Kita: Akhlak” Karya Muhammad Quraish Shihab - Khoiriyah, Khoiriyah; Ni’mah, Mamluatun; Herwati, Herwati (Asatiza: Jurnal Pendidikan, 2023)
This study aims to find out how moral education is according to the perspective of Muhammad Quraish Shihab in his book entitled "What we have lost: morals. The type of research used is qualitative research with library research methods, the data sources used are primary and secondary data sources, the data analysis technique used is content analysis. The results of this study indicate that moral education according to Quraish Shihab is divided into three, namely morals towards Allah, morals towards the Prophet Muhammad SAW and morals among fellow human beings. The moral values contained in the book are sincerity, grace, wisdom, reading, perseverance, trust, loyalty, strength, spaciousness, tolerance, nobility and self-esteem, discipline, simple living, shame and tabayyun.